(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research paper emphasizes the critical role of ‘Integrated Child Development Services (ICDS)’ in the healthy well-being, and nutrition of children and women. The ‘National Nutritious food security Act, 2013’entitles Anganwadi centers (courtyard shelters) responsible for ensuring mothers and children have access to food and nutrition. The program is widely regarded as a well-functioning intervention deserving of additional investment, but it is also a system that requires significantly greater coverage, quality, and impact to achieve acceleration in achieved outcomes. Additionally, the budget for 2021–22 allocates ’20,105 crores to the ICDS when combined with three other programs, compared to 20,532.4 crores to the ICDS alone last year; a highly regrettable reduction that does not bode well for service expansion. This research paper proposes several critical reforms necessary to revitalize the weakening Anganwadi system: 1. The budgetary allocation for ICDS should be considerably increased; 2. The market prices of the food and other supplements should be made the basis for fixing the mess charges.; 3. The Anganwadi workers aren’t recognized as Government servants and their pay is an honorarium. Just as the Kothari commission brought is drastic changes in the pay and perks of teachers in school education which improved the school education system, Anganwadi workers should be recognized as Government employees and their status should be that of early childhood teachers. This will attract more qualified and eligible workers to ICDS; 4. There were recent reports (UNICEF) that children in India are becoming increasingly anemic and deficient in vitamins. The New Education Policy, 2020 made it clear that the strengthening of the Anganwadi system is non-negotiable. Hence the paper focuses on the emergent need to equip Anganwadis with adequate infrastructure for ensuring nutritious food security amongst women and children in rural India.